Patient experiences of perioperative nutrition within an Enhanced Recovery After Surgery programme for colorectal surgery: a qualitative study. (2nd February 2016) - Short, V.; Atkinson, C.; Ness, A. R.; Thomas, S.; Burden, S.; Sutton, E.
Abstract: Aim: Nutrition is an important element of the Enhanced Recovery After Surgery (ERAS) programme. Patients have previously indicated that nutrition is a key component of ERAS that requires improvement. Our aim was to explore the perioperative nutrition experiences of colorectal surgical patients to identify barriers and facilitators to the integration of nutrition within ERAS. Method: Sixteen individuals undergoing colorectal surgery participated in a semi‐structured interview between postoperative day three and hospital discharge. The topic guide was developed iteratively throughout the study; topics included preoperative counselling, carbohydrate loading, fasting and postoperative nutrition. A constant comparison technique was employed during coding, and an inductive thematic analysis was used. Validity was ensured by double coding a sample of transcripts. Results: Findings are presented in the context of the following clinical themes: preoperative information, preoperative fasting, carbohydrate loading and nutritional drinks, postoperative diet and discharge. Individuals received too much general information which was repetitive, contradictory and not disease specific; this formed a key barrier affecting nutrition. Other barriers were negative experiences of nutritional drinks, stoma management, nausea and vomiting, and challenges from the hospital environment. Facilitators included interactions with staff, food accessibility and choice, and motivation for discharge. Conclusion: The key barrier to adherence of perioperative nutrition protocols was poor provision of information. Targeted information regarding postoperative diet, stoma management and coping with nausea and vomiting would be beneficial for colorectal surgical patients. Easily accessible food provided by ward staff was considered a facilitator.